Evolution statt Revolution - Elitennetzwerke seit der Perestrojka - Kuhr-Korolev, Corinna 1967- (Jahrbücher für Geschichte Osteuropas, 2024)
This issue focuses on the continuity of personal networks during the transition from the socialist era to the postsocialist phase. Using case studies, the authors explore the question of how particular groups within the social, political, or cultural elite of different former socialist countries were able to retain influence over certain areas of activity during the period of change in the late 1980s/early 1990s. Their contributions are based on newly discovered archive material and are conceptually linked by theories on the legacy of communism, social capital, and informality. Drawing on these theories, the authors deal with different thematic fields, from the transformation of the Soviet museum system to the development of the Georgian banking system, from property conflicts in Hungary to political thought in Slovakia.